97.2k views
2 votes
Please help somebody

Please help somebody-example-1
User Sewake
by
5.1k points

2 Answers

4 votes

Answer:

C

Explanation:

ok so, assuming that b cannot equal 0, we can divide it on both sides

(3a - 5)/c = b/b

anything divided by itself is 1

(3a - 5)/c = 1

multiply c:

3a - 5 = c

3a = c + 5

a = (c + 5)/3

User Nimesco
by
4.6k points
3 votes

Answer:

C.
(c+5)/(3)

Explanation:

Move b to the other side then b/b is 1

Move c to the other side it will become in the numerator

Move -5 to the other side it will be +5

So 3a = c+5

a =
(c+5)/(3)

User Dafang Cao
by
4.8k points